2016
DOI: 10.3949/ccjm.83a.15148
|View full text |Cite
|
Sign up to set email alerts
|

Best practices in LGBT care: A guide for primary care physicians

Abstract: Lesbian, gay, bisexual, and transgender (LGBT) people have unique healthcare needs. While all LGBT people are at an increased risk for mental health and substance abuse disorders, certain health conditions vary by group. Overweight and obesity are more common in lesbian and bisexual women, whereas sexual minority men are at increased risk for infections such as human immunodeficiency virus (HIV) and syphilis. Breast, cervical, and prostate cancer screening should be offered to all LGBT individuals according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 31 publications
1
38
0
3
Order By: Relevance
“…The attention to behavior and anatomy, in addition to identity, is supported by existing best practices in LGBT care and guidelines on taking routine sexual health histories. [16][17][18] Sexual orientation is a multidimensional construct encompassing identity, behavior, and attraction, with the potential for these components to act independently of and possibly incongruently with each other. [19][20][21][22][23][24] Prior research has identified that providers may make heteronormative assumptions about their patients and/or fail to ask their patients about their sexual orientation.…”
Section: Discussionmentioning
confidence: 99%
“…The attention to behavior and anatomy, in addition to identity, is supported by existing best practices in LGBT care and guidelines on taking routine sexual health histories. [16][17][18] Sexual orientation is a multidimensional construct encompassing identity, behavior, and attraction, with the potential for these components to act independently of and possibly incongruently with each other. [19][20][21][22][23][24] Prior research has identified that providers may make heteronormative assumptions about their patients and/or fail to ask their patients about their sexual orientation.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, primary care physicians are recommended to offer breast cancer screening to all transgender individuals in accordance with national guidelines [15]. Yet, the use of mammography in transgender individuals has not been adequately studied.…”
Section: Discussionmentioning
confidence: 99%
“…A lesbian, gay, bisexual, transgender, and queer (LGBTQ)-specific survey was adapted from several past studies that analyzed healthcare providers' attitudes, practices, and knowledge regarding LGBTQ health (Kelley et al, 2008;McNamara & Ng, 2016;Sanchez, Rabatin, 7 Sanchez, Hubbard, & Kalet, 2006;Shetty et al, 2016). This survey is a self-reporting, anonymous battery of demographics, measures, and experimental questions.…”
Section: Instrumentmentioning
confidence: 99%
“…Social and medical inequality pervades LGBT communities as evidenced by barriers that include lower incomes (Jackson, Agenor, Johnson, Austin, & Kawachi, 2016; Lee Badgett, Durso, & Schneebaum, 2013), lower rates of insurance (Buchmueller & Carpenter, 2010;Krehely, 2009), limited number of culturally-competent providers (Dahlhamer, Galinsky, Joestl, & Ward, 2016;Hutchinson, Thompson, & Cederbaum, 2006;Mayer et al, 2008), lack of nondiscriminatory policies (Institute of Medicine, 2011), stigmatization (Daniel, Butkus, & Health and Public Policy Committee of the American College of Physicians, 2015), and even direct refusal of care (Grant et al, 2010;James et al, 2016). In relation to these individual and systemic barriers, numerous studies have revealed that LGBT people are more likely to identify themselves with poorer health conditions than their heterosexual counterparts (Daniel et al, 2015;Grant et al, 2010;Institute of Medicine, 2011;Jackson et al, 2016;James et al, 2016;McNamara & Ng, 2016). For example, LGBT individuals are 1.5 times more likely to suffer from anxiety and depression, lesbian women are 3 times more likely to have alcohol and substance use disorders, gay men are 1.6 times more likely to develop drug-use disorders (McNamara & Ng, 2016), and 40% of transgender adults have attempted suicide (Grant et al, 2010;James et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation